Obesity and dyslipoproteinemia - Garmendia Lorena, Fausto (2017)
The definition, main general causes, quantification and body distribution of obesity are described. A general review of the different blood lipoprotein fractions as well as the procedure for the diagnosis of dyslipoproteinemia is done. Dyslipoproteinemia of obesity is a secondary form of insulin resistance as a result of lowering of lipoprotein lipase activity resulting in increase of triglycerides, decrease of HDL cholesterol, and establishment of the metabolic syndrome. Its pathophysiology and the development of obesity related morbidities are described. Dyslipoproteinemia of obesity is present in both the basal and postprandial status. An attempt is made to estimate the prevalence of dyslipoproteinemia. Treatment is outlined and includes change in lifestyle regarding diet and physical activity, pharmacotherapy, and bariatric surgery, as well as the hypolipidemic treatment.